2018
DOI: 10.1177/1756286418774338
|View full text |Cite
|
Sign up to set email alerts
|

Phase IV study of retention on fingolimod versus injectable multiple sclerosis therapies: a randomized clinical trial

Abstract: Objective:In relapsing–remitting multiple sclerosis (RRMS), suboptimal adherence to injectable disease-modifying therapies (iDMTs; interferon β-1a/b, glatiramer acetate) is common, reducing their effectiveness. Patient retention on oral fingolimod and iDMTs was evaluated in PREFERMS, a randomized, parallel-group, active-controlled, open-label, 48-week study.Methods:Patients were included if they had RRMS, were aged 18–65 years and had Expanded Disability Status Scale score up to 6, enrolled at 117 US study sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 37 publications
7
42
0
Order By: Relevance
“…Our result has been supported by the LONGTERMS trial, an open‐label, single‐arm, long‐term extension study ( n = 2355) in which the results demonstrated that low rates of brain volume loss were sustained for up to 6 years of fingolimod treatment . All the three trials that compared fingolimod with DMTs used the dose of 0.5 mg/d, and fingolimod was found to be more effective than DMTs.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Our result has been supported by the LONGTERMS trial, an open‐label, single‐arm, long‐term extension study ( n = 2355) in which the results demonstrated that low rates of brain volume loss were sustained for up to 6 years of fingolimod treatment . All the three trials that compared fingolimod with DMTs used the dose of 0.5 mg/d, and fingolimod was found to be more effective than DMTs.…”
Section: Discussionmentioning
confidence: 91%
“…Of 1495 publications returned from the literature search, ten studies with a total of 6547 patients met the inclusion criteria. The selection process is depicted in the flow diagram (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations